PENGARUH LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN KONTRUKTIVISME PADA MATERI EKOSISTEM TERHADAP HASIL BELAJAR SISWA KELAS VII SMP - Widia Setia Dewi; Arnentis Arnentis; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research has been carried out in Pekanbaru N 12 Middle School from January to March 2019 which aims to determine the implementation of the constructivism approach to science learning in grade VII students of junior high school using the quasi-experimental technique. The sample used in this study is class VII 2 and VII 3, which amount to each class 32 while the population is all students of class VII SMP N Pekanbaru. The instruments used are learning tools in the form of syllabus, learning implementation plans (RPP), student worksheets based on constructivism approaches. The results showed that the LKPD based on the constructivism approach had an effect on learning outcomes indicating that the control class with a pretest average of 30.54, while in the experimental class with an average value of 31.40 with the pretest category in the two classes "Very poor" at interval <34, this shows that at the beginning of learning before learning or treatment is given both classes have a mean that is not much different. While the average value of posttest in contriol class 78.90 with the category "Enough" at the interval value of 55-64 and in the experimental class the mean value was 88.12 with the category "Very Good" which at intervals 85-100. It can be concluded that the effect of LKPD based on the constructivism approach can improve the learning outcomes of class VII students of SMP N Pekanbaru.Key Words: LKPD Based on Constructivism Approach, Learning Outcomes, Science Learning